THE CORRELATION BETWEEN POE LEARNING MODEL AND CRITICAL THINKING ABILITY OF STUDENTS IN PAI AND BUDI PEKERTI SUBJECT - Zabrina, Rahma (Tarbiyah Islamiyah: Jurnal Ilmiah Pendidikan Agama Islam, 2024)
This research aims to find out: (1) The application of the Predict, Observe, and Explain (POE) learning model in the subject of Islamic Religious Education & Budi Pekerti class VII at SMP Negeri 2 Waru. (2) The level of critical thinking ability of students in the subject of Islamic Religious Education & Ethics class VII at SMP Negeri 2 Waru. (3) The correlation between the application of the Predict, Observe, and Explain (POE) learning model in Islamic Religious Education & BP subjects with an increase in the critical thinking skills of seventh grade students at SMP Negeri 2 Waru. The method used in this research is field research with a quantitative approach with correlational techniques. The population in this study amounted to 344 students and a sample of 60 students. The data collection techniques used are observation, documentation, and questionnaires. As for the instrument prerequisite test using validity and reliability tests and hypothesis testing using product moment correlation tests and significance tests. The results of this study indicate that the application of the POE model in PAI & BP subjects is in the good category with an average of 79%. The level of critical thinking skills of students in PAI & BP subjects in class VII of 70% is in the good category. And the correlation test results obtained r_hitung of 0.671. At the 1% and 5% significance levels the results of r_ (count) > r_table so it can be concluded that H_0 is rejected and H ‘a’ which reads there is a correlation between the application of the critical thinking mode and the critical thinking mode.